The peach volatilome modularity is reflected at the genetic and environmental response levels in a QTL mapping population - Sanchez, Gerardo; Martinez, José; Romeu Santacreu, José Francisco; García Brunton, Jesús; Monforte Gilabert, Antonio J.; Badenes, María Luisa; Granell Richart, Antonio (2017)
Background: The improvement of fruit aroma is currently one of the most sought-after objectives in peach breeding programs. To better characterize and assess the genetic potential for increasing aroma quality by breeding, a quantity trait locus (QTL) analysis approach was carried out in an F1 population segregating largely for fruit traits. Results: Linkage maps were constructed using the IPSC peach 9 K Infinium ® II array, rendering dense genetic maps, except in the case of certain chromosomes, probably due to identity-by-descent of those chromosomes in the parental genotypes. The variability in compounds associated with aroma was analyzed by a metabolomic approach based on GC-MS to profile 81 volatiles across the population from two locations. Quality-related traits were also studied to assess possible pleiotropic effects. Correlation-based analysis of the volatile dataset revealed that the peach volatilome is organized into modules formed by compounds from the same biosynthetic origin or which share similar chemical structures. QTL mapping showed clustering of volatile QTL included in the same volatile modules, indicating that some are subjected to joint genetic control. The monoterpene module is controlled by a unique locus at the top of LG4, a locus previously shown to affect the levels of two terpenoid compounds. At the bottom of LG4, a locus controlling several volatiles but also melting/non-melting and maturity-related traits was found, suggesting putative pleiotropic effects. In addition, two novel loci controlling lactones and esters in linkage groups 5 and 6 were discovered. Conclusions: The results presented here give light on the mode of inheritance of the peach volatilome confirming previously loci controlling the aroma of peach but also identifying novel ones.